Human Rights as an inspiring principle of the Spanish foreign policy: the humanitarian visa - Pertusa Rodríguez, Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The 2015 refugee crisis and the 2021 Afghan crisis have reopened the debate on how the EU and its Member Sates are fulfilling their commitments on Human Rights. In this regard, the EU has taken its responsibilites on visas, migration and asylum under the umbrella of the Area of Freedom, Security and Justice. On the other hand, several scholars have suggested that both the LTV and the airport transit visa should become humanitarian permits. Regarding the Spanish legal framework, it has been required a more proactive application of section 38 of the 12/2009 Act. However, the debate should not focus on creating new permits or redirecting the existing ones. Since both solutions have been used whenever the States have decided to do so. In this way, the decision on humanitarian visas is not so much a matter of legal technique but rather of political will.
Keywords: Human Rights; asylum; European Union; humanitarian visas; sovereign nation